Perspectives on Clinicians' Roles and Postpartum Opioid Pain Management: A Qualitative Analysis - Merchant, Tazim; DiTosto, Julia D.; Soyemi, Elizabeth; Yee, Lynn M.; Badreldin, Nevert (American Journal of Perinatology, 2025)
Pain is a common postpartum complaint, yet data suggest that approaches to postpartum pain management vary widely. Given the goal of improving quality and equity in postpartum pain management, we aimed to examine whether and how clinicians' perspectives on postpartum pain management differed by clinician roles.This is a qualitative study at a large, tertiary, and academic medical center. From November 2021 to June 2022, obstetric clinicians, including attending physicians, trainee physicians, and advanced practice providers (APPs), were recruited to complete in-depth interviews regarding their clinical experience managing postpartum pain using a semi-structured interview guide. Participants were asked to reflect both on their own role and that of the other clinician types. Purposive sampling was used to enroll a cohort representative of the institutional workforce in terms of clinician type and demographics. Data were analyzed using the constant comparative method.Of 46 participants, 47.8% (n = 22) were attending physicians, and 91% (n = 42) were female. Emergent themes were both self-reflected and externally directed. Data demonstrated that postpartum pain management differs by clinician type and level of experience. Themes related to the role of attending physicians included responsibilities as teachers for trainees, supervisory roles, and perceptions that attendings have greater comfort with prescribing opioids. Themes related to the role of trainee physicians included the impact of patient load on trainees' management, limitations of morning rounds, familiarity with emerging data, and perceptions of hesitancy to prescribe opioids. Themes related to the role of APPs included less reliance on opioids for postpartum pain management and emphasis on nonpharmacological approaches.Perspectives on postpartum pain management vary by clinician role. Consideration of these differences and the interplay between roles is essential when examining opioid prescribing patterns and developing interventions to improve postpartum pain management.
Keywords: postpartum pain management; clinician role; opioid prescribing